No effect of deleted in malignant brain tumors 1 deficiency on chemotherapy induced murine intestinal mucositis - Anders B. Nexoe (Nature Portfolio, 2021)
Abstract Mucositis is a serious adverse effect of chemotherapeutic treatment. During intestinal mucositis, the mucosal barrier is compromised, increasing the risk of severe infections. Mucositis necessitates dose reduction or pauses in treatment, which affect the outcome of the treatment. Deleted in malignant brain tumors 1 (DMBT1) is a secreted scavenger protein with effects on innate immunity and epithelial regeneration. We have previously shown that jejunal DMBT1 expression is increased in piglets during chemotherapeutic treatment. We hypothesized that DMBT1 ameliorates doxorubicin-induced mucositis. Individually-caged Dmbt1 +/+ (WT) and Dmbt1 −/− (KO) female mouse littermates received intraperitoneal injections of either doxorubicin or saline. They were euthanized after three (D3) or seven days (D7). Weight loss was monitored every day, and serum citrulline levels were measured at termination. Intestinal tissue was analyzed for the expression of DMBT1 and proinflammatory cytokines (IL-1β, IL-6, and TNF). Specimens from the small intestines and colon were scored for inflammation and epithelial and mucosal architecture changes. We detected no effect of DMBT1 on weight loss, serum citrulline levels, expression of proinflammatory cytokines, or histologic damage. We detected a significant increase in crypt depth in WT mice compared to that in KO mice on D3. In conclusion, DMBT1 does not affect doxorubicin-induced mucositis in mice.